In Vitro Evaluation of the Anti-Bacterial Activity of Aloe Vera and Mint Extract against Bacterial Isolates from Facial Acne - Baral, Soma Kanta; Bhaila, Nabina; Bhasima, Samita (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Acne is a common dermatological condition often associated with bacterial colonization, primarily Staphylococcus aureus and Staphylococcus epidermidis. The increasing resistance to conventional antibiotics has prompted the exploration of plant-based alternatives. This study investigates the antibacterial effects of Aloe vera extract and Mentha spicata essential oil on acne-associated bacterial isolates.Method: A cross-sectional, laboratory-based study was conducted involving 51 facial acne samples. Bacterial isolates were identified using standard biochemical tests. Mentha spicata essential oil was obtained via hydro-distillation, while Aloe vera extract was prepared using hot air oven drying followed by dissolution in Dimethyl sulfoxide. The antibacterial activity was assessed using the agar well diffusion method.Result: Out of 51 acne samples, 48 (94.11%) showed bacterial growth. Staphylococcus epidermidis was the most common isolate, followed by Staphylococcus aureus including Methicillin-resistant (MRSA) and Methicillin-sensitive (MSSA) strains. Mentha spicata essential oil exhibited an antibacterial effect against 81.13% of isolates (MIC and MBC: 25 µL/mL), while Aloe vera extract was active against 58.5% (MIC and MBC: 50 µL/mL).Conclusion: Both Aloe vera and Mentha spicata demonstrated inhibitory effects against acne-associated bacteria. The stronger antibacterial activity of mint essential oil suggests its greater therapeutic potential in acne management.